2017
DOI: 10.1080/21505594.2016.1278334
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of pneumococcal surface protein K, a potential pneumococcal vaccine antigen

Abstract: The pneumococcal capsule is indispensable for pathogenesis in systemic infections; however, many pneumococcal diseases, including conjunctivitis, otitis media, and some systemic infections in immunocompromised patients, are caused by nonencapsulated Streptococcus pneumoniae (NESp). Null capsule clade 1 (NCC1), found in group 2 NESp, expresses pneumococcal surface protein K (PspK) and is becoming prevalent among pneumococcal organisms owing to the widespread use of pneumococcal conjugate vaccines. Despite its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…ANXA2 has been shown to be involved in efficient bacterial invasion of epithelial cells by pathogens such as Rickettisa, Mycoplasma pneumoniae, and Pseudomonas aeruginosa [52,53]. In addition to our findings, another group also demonstrated that pneumococcal surface protein K (PspK) interacts with ANXA2 and promotes adherence to lung epithelial cells [54]. Furthermore, a previous study demonstrated that PsaA also interacts with E-cadherin expressed on nasopharyngeal epithelial cells [18].…”
Section: Discussionsupporting
confidence: 82%
“…ANXA2 has been shown to be involved in efficient bacterial invasion of epithelial cells by pathogens such as Rickettisa, Mycoplasma pneumoniae, and Pseudomonas aeruginosa [52,53]. In addition to our findings, another group also demonstrated that pneumococcal surface protein K (PspK) interacts with ANXA2 and promotes adherence to lung epithelial cells [54]. Furthermore, a previous study demonstrated that PsaA also interacts with E-cadherin expressed on nasopharyngeal epithelial cells [18].…”
Section: Discussionsupporting
confidence: 82%
“…In conclusion, the study of Jang et al. shows the potential of PspK as vaccinate candidate, 11 thereby also confirming earlier work from Keller et al. (2015).…”
supporting
confidence: 82%
“…showed furthermore that vaccination with R3 induced protection, showing the strongest effects measured after intranasal immunization. 11 Despite the variability of PspK, antibodies raised against this protein cross-reacted with 79% of the encapsulated strains not containing PspK. This cross-reactivity is likely due to recognition of domains of distantly related proteins, such as PspC and PspA, therefore much higher cross-reactivity is expected with PspK containing NESp.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding nasopharyngeal colonization and the importance of NE Sp in this niche, Jang and colleagues demonstrated that R3 domain of PspK may be an effective vaccine candidate for both NE Sp and encapsulated S. pneumoniae . The immunization with R3 or UD: R3 of PspK elicited effective humoral and mucosal immune responses against nasopharyngeal colonization and the subsequent development of AOM and pulmonary infection in mice [ 75 ].…”
Section: Current Strategies In the Development Of Pneumococcal Promentioning
confidence: 99%